The experiences of black women undertaking doctoral studies at a South African University - Ts’ephe, Lifutso (University of the Free State, 2014)
This dissertation builds on and contributes to work in the fields of higher education and the capabilities approach. Specifically, it investigates the educational biographies of a small number (n=7) of black women who were either in their final year of doctoral study or had graduated recently at the time of the interviews. Although a number of studies (e.g. Acker, 1980; Magano, 2011; Pillay, 2009; Prozesky, 2008) have investigated women in academia, there has not been a strong focus on the experiences of black women in doctoral studies, and even less so on South African students. The available studies show that students leave doctoral programmes prematurely due to a number of reasons, for example, an inability to manage time effectively, financial constraints, demotivation and depression, and poor supervision (Magano, 2011). Pillay (2009) adds that the balancing of two lives, being a mother and an employee, generates further challenges. As part of its National Development Plan, South Africa’s National Planning Commission aims to not only rapidly increase the number of doctoral graduates, but to also promote postgraduate education for marginalised groups within the next 15 years. In 2012, black women represented 2 294 (16.4%) of all doctoral enrolments in the country, which is a significant increase from the 468 (7.5%) who enrolled for doctoral studies in the year 2000. The current research draws conceptually on the capabilities approach, developed by Amartya Sen and Martha Nussbaum. This framework was chosen because it is used mainly to evaluate and assess an individual’s well-being, as well as the social arrangements that foster or hinder this well-being. The capabilities approach, therefore, includes issues such as the design of policies and proposals for social change within societies (Robeyns, 2005) and relates the evaluation of the quality of life to the assessment of the capability to function; that is, to be and do in ways which are valued by an individual. A qualitative approach was adopted for the study as the most suitable method. A case study design allows the researcher to emphasise the experiences of the individual, as well as the social arrangements which help or hinder each individual’s success. In-depth information regarding the participants’ social experiences was also gathered. The issue that was explored in this study was black women’s experience of doctoral study – the highs, the lows, and the challenges. The assumption was that gender plays a significant role in shaping the educational lives of these women. In the study, gender is understood as the social organisation of the relations between the sexes, differentiating the social meaning that is attributed to sexual differences from the sexual differences themselves (Robeyns, 2005). Exploring these women’s experiences revealed the developmental outcomes of doctoral education they value, the opportunities to reach these outcomes they appreciated, and the personal, social and environmental factors which influenced their ability to use the developmental opportunities. The findings from this study could lead to recommendations to higher education institutions with regard to increasing the enrolment and retention of this marginalised group. These recommendations could also contribute to improving policies which attract and retain more black women doctoral students in higher education.

Hierdie verhandeling bou voort op en lewer ’n bydrae tot vorige navorsing in die velde van hoër onderwys en die vermoënsbenadering. Die studie ondersoek spesifiek die opvoedkundige biografieë van ’n klein aantal (n=7) swart vroue wat ten tye van die onderhoude óf in hulle finale jaar van doktorale studie was óf onlangs gegradueer het. Alhoewel daar tog ’n aantal studies (vgl. Acker, 1980; Magano, 2011; Pillay, 2009; Prozesky, 2008) is wat vroue in die akademie ondersoek, is daar nog nie ’n sterk fokus geplaas op die belewenisse van swart vroue in doktorale studie, en nog minder op Suid-Afrikaanse studente, nie. Studies toon dat studente hulle doktorale studie weens ’n aantal redes staak, byvoorbeeld ondoeltreffende tydsbestuur, finansiële beperkings, demotivering en depressie, asook swak studieleiding (Magano, 2011). Pillay (2009) noem ’n verdere uitdaging, naamlik om ewewig te bewerkstellig tussen om ’n ma te wees en om ’n werknemer/student te wees. As deel van sy Nasionale Ontwikkelingsplan, poog ons land se Nasionale Beplanningskommissie om nie net die aantal doktorale gegradueerdes beduidend te vermeerder nie, maar om ook nagraadse opvoeding onder gemarginaliseerde groepe binne die volgende 15 jaar te bevorder. In 2012 het swart vroue 2 294 (16,4%) van alle doktorale inskrywings uitgemaak, ’n beduidende toename van die 468 (7,5%) swart vroue wat in 2000 vir doktorale studie ingeskryf het. Die navorsing in hierdie studie put op konseptuele vlak uit die vermoënsbenadering wat deur Amartya Sen en Martha Nussbaum ontwikkel is. Dié raamwerk is uiters geskik omdat dit hoofsaaklik fokus op die evaluering en assessering van ’n individu se welsyn, asook op die sosiale organisering wat hierdie welsyn bevorder of belemmer. Dit behels dus onder meer die ontwerp van beleid en voorstelle vir sosiale verandering binne samelewings (Robeyns, 2005) en bring die evaluering van lewensgehalte met die assessering van die vermoë om te funksioneer, in verband. Om te funksioneer, in hierdie konteks, beteken om die mens te wees en die dinge te doen wat jy hoog op prys stel. ’n Kwalitatiewe benadering is in die studie gevolg as die mees geskikte metode. Met ’n gevallestudie-ontwerp kan die klem gelê word op die ervarings en vereistes van die individu, asook die sosiale organisering wat elke persoon se sukses bevorder of belemmer. Diepgaande inligting rakende die deelnemers se sosiale belewenisse is ook ingesamel. Die kwessie wat in die navorsing verken is, is swart vroue se belewenisse van doktorale studie – die hoogtepunte, die laagtepunte en die uitdagings. Die veronderstelling was dat gender ’n beduidende rol speel in die vorming van hierdie vroue se opvoedkundige lewe. In hierdie studie word gender verstaan as die sosiale organisering van die verhoudings tussen die geslagte, waar die sosiale betekenis wat aan geslagsverskille toegeskryf word van die geslagsverskille op sigself onderskei word (Robeyns, 2005). Die verkenning van hierdie vroue se belewenisse het verskeie bevindings gelewer: die ontwikkelingsuitkomste van doktorale opvoeding wat hulle as waardevol beskou; die geleenthede wat hulle as waardevol beskou om hierdie uitkomste te bereik; en die persoonlike, sosiale en omgewingsfaktore wat hulle vermoë beïnvloed het om die ontwikkelingsgeleenthede te benut. Die studie se bevindings kan lei tot aanbevelings vir hoëronderwysinstansies rakende die toename in inskrywings en die behoud van hierdie gemarginaliseerde groep. Hierdie aanbevelings kan ’n bydrae lewer tot die verbetering van beleid ten einde die aantal swart vroulike doktorale studente in hoër onderwys te verhoog en hulle te behou.
Dissertation (M.A. (School of Higher Education Studies))--University of the Free State, 2014
Keywords: Gender; Race; Capabilities approach; Doctoral students; Academic mothers; Women -- Education -- South Africa; Women, Black -- Education -- South Africa